The hierarchy of the essential verb categories in Zulu - Posthumus, L. C. (South African Journal of African Languages, 1993)
The aim of this article is to determine the hierarchical arrangement of the essential verb categories mood, tense, time and actuality. The mutual dependency of these verbal categories is determined. The subcategories found in each of these major categories are investigated in order to establish their mutual exclusiveness. Apart from the realization of these categories in the main verb, their realization in the copulative verb is also determined. The copulative verb has a further essential category, namely implication which realizes as a binary opposition inchoative versus non-inchoative. It is imperative to establish the mutual dependency and hierarchy of the essential verb categories for an exhaustive discussion of the verb, an area which has hitherto been sadly neglected.